Enhanced depth imaging optical coherence tomography features of two types of Vogt–Koyanagi–Harada disease: fuzzy or lost pattern of the choroidal vasculature is of diagnostic value - Liu, Xinshu; Wang, Shuling; An, Yan; Zhang, Hao (Frontiers in Medicine, 2024)
Objective: To compare enhanced depth imaging optical coherence tomography (EDI-OCT) features of exudative retinal detachment (ERD) type and optic disc (OD) swelling type Vogt-Koyanagi-Harada (VKH) disease. METHODS: Hospitalized VKH patients were retrospectively reviewed and classified into ERD type and OD swelling type. EDI-OCT features were analyzed. RESULTS: 32 ERD type and 15 OD swelling type VKH patients at the acute uveitis stage were included. The interval between ocular symptom onset and treatment start in OD swelling type VKH disease was significantly longer than that in ERD type (p<0.001). Fuzzy or lost pattern of the choroidal vasculature was observed in 100% VKH patients of both types, moreover, high frequencies (greater than or equal to 50%) of fluctuations in the internal limiting membrane, interdigitation zone disruption, ERD, retinal pigment epithelium (RPE) folds and ellipsoid zone disruption were observed in both types. OD swelling type VKH disease had higher frequencies of OD swelling and hyperreflective substances above the RPE (p<0.001 and p=0.003, respectively) and lower frequencies of ERD and bacillary layer detachment (BLD) (p=0.012 and p<0.001, respectively). At the convalescence stage, changes of EDI-OCT image in 10 ERD type and 5 OD swelling type VKH patients were analyzed. The frequencies of the OCT features declined with similar trends in both types of VKH disease. CONCLUSION: Although ERD type and OD swelling type VKH disease have their own unique characteristics, they share common EDI-OCT features. Fuzzy or lost pattern of the choroidal vasculature that indicates choroidal inflammation may serve as a diagnostic aid for VKH disease, especially for the OD swelling type and early-stage ERD type.